2020
DOI: 10.1093/biolre/ioaa083
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-based genome editing in mice uncovers 13 testis- or epididymis-enriched genes individually dispensable for male reproduction†

Abstract: Developing a safe and effective male contraceptive remains a challenge in the field of medical science. Molecules that selectively target the male reproductive tract and whose targets are indispensable for male reproductive function serve among the best candidates for a novel non-hormonal male contraceptive method. To determine the function of these genes in vivo, mutant mice carrying disrupted testis- or epididymis-enriched genes were generated by zygote microinjection or electroporation of the CRISPR/Cas9 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…The mating results indicated that epididymal and ejaculated spermatozoa may have different fertility properties. Our findings were consistent with a recent study that Cabs1 KO mice were still sterile but the number of pups and litters were significant less than WT controls [ 13 ]. However, no other reproductive phenotypes were reported in their study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mating results indicated that epididymal and ejaculated spermatozoa may have different fertility properties. Our findings were consistent with a recent study that Cabs1 KO mice were still sterile but the number of pups and litters were significant less than WT controls [ 13 ]. However, no other reproductive phenotypes were reported in their study.…”
Section: Discussionsupporting
confidence: 93%
“…The calcium-binding properties of Cabs1 are well-established. A very recent study just showed that Cabs1-deficient mice are fertile to a certain extent [ 13 ]. However, the further physiological roles of Cabs1 in the male reproductive system have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To unveil the factor(s) involved in mitochondrial sheath formation, creating and analyzing male mice carrying null mutations is a feasible approach because we can observe protein function directly, and as yet no culture systems exist that produce fully functional spermatozoa in vitro. Therefore, we generated knockout (KO) male mice using CRISPR/Cas9-based genome engineering and screened their phenotypes ( 10 12 ) to find factors involved in mitochondrial sheath formation. In addition, we analyzed the functions of identified proteins to unveil the molecular mechanisms of mitochondrial sheath formation.…”
mentioning
confidence: 99%
“…Fertile and without any phenotypic change(s) 2020 [31] FSH-follicle-stimulating hormone; LH-luteinizing hormone; FG-full-grown; hCG-human chorionic gonadotropin; 11-KT-11-Ketotestosterone; E2-estradiol; LHβ-luteinizing hormone beta polypeptide; MMAF-multiple morphological anomalies of the sperm flagella.…”
Section: Methodsmentioning
confidence: 99%
“…Among all one thousand genes assumed to have a role in fertility and hypotheses issued, partially proved to be dispensable since over forty-five genes knockout did not affect the host’s homeostasis [ 29 , 30 , 31 ]. For example, spermatogenesis associated 16 (Spata16), actin-like 7A (ACTL7A), or Zfy1/2-DKO mice are among the many others that are crucial for fertility.…”
Section: Crispr/cas9 and Infertilitymentioning
confidence: 99%